Hot pot murder - Chow, Jennifer J. (Chow, Jennifer J. L.A. night market mysteries, 2023)
When the president of the restaurant owners association dies during a group dinner, everyone at the meal is a suspect, and cousins Yale and Celine Yee stir the pot as they investigate the dinner attendees to keep their friends and family out of hot water.